2019
DOI: 10.21451/1984-3143-ar2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Storage of boar semen at 16-18 °C in the long-term commercial extender prepared with deionized water or nanowater

Abstract: The aim of this study was to assess the usefulness of nanowater (NW; water declusterized using cold plasma treatment) as a diluent for a commercial boar semen extender during the 15-day storage (Days 1 to 15) at 16-18 °C. Ejaculates collected from 8 boars were subjected to the standard evaluation and then diluted in the extender prepared with deionized water (DW) or NW to a final concentration of 3×10 9 spermatozoa/ml. The proportion of defective spermatozoa increased (P<0.05) from Day 10 to Day 15 of storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…Thus, it was demonstrated that water stimulated growth and pathogenicity of entomopathogenic fungi used as biopesticides [28]. Murawski et al described benefits of cryopreservation of ram [29] and boar [30] semen in GP-treated water. The barley malt quality could be improved when GP-treated water was applied [31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was demonstrated that water stimulated growth and pathogenicity of entomopathogenic fungi used as biopesticides [28]. Murawski et al described benefits of cryopreservation of ram [29] and boar [30] semen in GP-treated water. The barley malt quality could be improved when GP-treated water was applied [31].…”
Section: Introductionmentioning
confidence: 99%
“…Lake 희석액은 sodium glutamate monohydrate 1.92 g, glucose 0.6 g, magnesium acetate tetrahydrate 0.08 g, tri-potassium citrate monohydrate 0.128 g, sodium acetate 0.51 g을 100 mL 초순수에 용해하여 제조하였다 (Lake, 1960;Lake and Ravie, 1979). (Szymanowicz et al, 2019;Blackburn et al, 2009)…”
Section: 시약 및 희석액의 조성mentioning
confidence: 99%
“…Similarly, fermentative microorganisms are stimulated by LPGPA, providing quality improvement of brewery barley and malt [42]. Murawski et al [43] and Szymanowicz et al [44] demonstrated successful application of LPGPA in animal breeding. Ram and boar semen preserved in plasma treated water provided more efficient insemination.…”
Section: Introductionmentioning
confidence: 99%